The Hoffmeister asteroid family - Carruba, V. [UNESP]; Novaković, B.; Aljbaae, S. [UNESP] (My University, 2017)
The Hoffmeister family is a C-type group located in the central main belt. Dynamically, it is important because of its interaction with the ν1C nodal secular resonance with Ceres, which significantly increases the dispersion in inclination of family members at a lower semimajor axis. As an effect, the distribution of inclination values of theHoffmeister family at a semimajor axis lower than its centre is significantly leptokurtic, and this can be used to set constraints on the terminal ejection velocity field of the family at the time it was produced. By performing an analysis of the time behaviour of the kurtosis of the νW component of the ejection velocity field [γ 2(νW)], as obtained from Gauss' equations, for different fictitious Hoffmeister families with different values of the ejection velocity field, we were able to exclude that the Hoffmeister family should be older than 335 Myr. Constraints from the currently observed inclination distribution of the Hoffmeister family suggest that its terminal ejection velocity parameter VEJ should be lower than 25ms-1. Results of aYarko-YORP Monte Carlo method to family dating, combined with other constraints from inclinations and γ 2(νW), indicate that the Hoffmeister family should be 220-40 +60 Myr old, with an ejection parameter VEJ = 20 ± 5 m s-1.
Keywords: Asteroids: general; Asteroids: individual: Hoffmeister; Celestialmechanics; Minor planets